Comparing Second Language Identity as Experienced by International Students during Their Studying abroad - Irvan Ruslan Bennu (Research And Innovation In Language Learning (RILL), 2021)
Language and cultural identity are things that can be summarized in terms of language identity. The construct of a second language identity has a strong relation with study abroad. Second language identity tends to appear in continuous classical conditioning through study abroad. However, no further investigation about this issue has been researched in Indonesian international student context. This study purposed to explore how is the second language identity constructed through the interactions during study abroad. Through narrative interviews, this study will explore more about how second language identity of two international students constructed in their study abroad countries. The result of this study is second language identity construction is more powerful based on self-desire of participants and who the interlocutors are. Further, by knowing how the second language identity is constructed when international students are in native and non-native English-speaking countries, this study will give an empirical contribution about how English language learning patterns depend on the environment. Thus, the English teacher or language expert later could adapt English learning patterns through the construction of other people's language identity.